Enhancing Risk Management in the SPALD Project - Hasan, Nining Ardiyanti; Hidayat, Acep; Amin, Mawardi (Universitas Ibn Khaldun Bogor, 2025)
The SPALD Project is currently undergoing a survey phase to gather data on perceptions and experiences related to risks. Data analysis has been conducted using statistical methods to explore the relationship between risk identification and risk management effectiveness in the context of the SPALD project. The analysis results indicate a significant positive correlation between risk identification and risk management effectiveness, with a correlation coefficient of 0.75 (p < 0.01). Regression analysis indicates that the risk identification variable significantly predicts risk management effectiveness (F(1, 123) = 64.32, p < 0.001), with a coefficient of determination (R squared) of 0.52. These findings affirm that enhancing the risk identification process meticulously and comprehensively can enhance risk management effectiveness in the SPALD project in DKI Jakarta. Recommendations for this project include initial risk identification, the use of adaptive risk management systems, implementation of analysis-based mitigation strategies, and team awareness enhancement. These recommendations aim to enhance risk management effectiveness, achieve project objectives, and mitigate potential negative impacts.